Experimental salmonellosis caused by salmonella enteritidis phage types 1, 4 and 7 in quails (Coturnix coturnix japonica) - Öztürk, G; Yilmaz, F; Kalender, H (Scientific Technical Research Council Turkey, 1999)
In this study, S.enteritidis PT1, 4 and 7 strains isolated from chickens were used. Suspensions containing 10(9) bacteria were inoculated orally to 45 quails. Pathological lesions were examined and bacterial isolation were performed during about 30 days. In 3(rd) days of experiment, one quail died in PT1 group. In macroscopic examinations, hyperemia and change of colour in liver and slight enlargement in spleen were observed. In microscopic examinations, degeneration, necrose and typhoid nodes were seen in liver. There were reticular cell hyperplasia in spleen and epithelial degeneration, lenfoid hyperplasia in intestines. Bacteria was able to isolated from intestines, liver and spleen in quails inoculated with PT1 and PT4. Only intestinal isolation was able to performed in PT7 group during experiment After 23(rd) days of inoculation any phage types of bacteria was not isolated.
Salmonella enteritidis Faj Tip 1, 4 ve 7 ile Bildircinlarda (Coturnix coturnix japonica) Oluşturulan Deneysel Salmonellosis
Keywords: S.enteritidis; phage types; quail; pathology; experimental infection